REVISITING JAVANESE ISLAM - Kabir, Gedong Maulana (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
This article tends to revisiting Javanese Islamic studies. This study began from the European travelers’ period who noted some aspects of society such as the religious life. Those notes show the negative label that is addressed to the Javanese religious practices. These negative labels are often reproduced in Javanese Islam studies to this day. This article argues that the negative labels in Javanese Islamic studies tend to be misrepresentative. These kinds of results cannot be separated from certain paradigms in religious studies. There are two paradigms in the study of religion which are discussed in this article. First, the world religion paradigm. This paradigm, consciously or not, is often used in Javanese Islamic studies. The implication is Javanese religious practices are often portrayed as animist, syncretic, and so on. Second, the indigenous religion paradigm. This article elaborates this paradigm because of its potential in understanding Javanese Islamic religious practice more properly. The basis of this paradigm is intersubjective relation with ethical commitment, responsibility, and reciprocity.